2022
DOI: 10.3390/children9060858
|View full text |Cite
|
Sign up to set email alerts
|

Screening Accuracy of FeNO Measurement for Childhood Asthma in a Community Setting

Abstract: (1) Background: The exhaled fractional nitric oxide is a well-recognized biomarker used in clinical settings for controlling and managing asthma. Less is known about the value of Fractional Exhaled Nitric Oxide (FeNO) measurement in epidemiological studies on childhood asthma, although available evidence suggests that an increased FeNO is associated with an increased risk of asthma. (2) Aim: The aim of the study was to assess FeNO accuracy in the identification of children with asthma, participants in a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(48 reference statements)
0
3
1
Order By: Relevance
“…Contrastingly, in a prior study conducted by the author, the conclusion reached was that FeNO measurement was not an effective screening tool for pediatric asthma in a community setting [23]. However, the findings of the present study contradict this, indicating that children exhibiting asthma-like symptoms and elevated FeNO levels are at an increased risk of asthma, and these findings suggest the need for additional investigation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrastingly, in a prior study conducted by the author, the conclusion reached was that FeNO measurement was not an effective screening tool for pediatric asthma in a community setting [23]. However, the findings of the present study contradict this, indicating that children exhibiting asthma-like symptoms and elevated FeNO levels are at an increased risk of asthma, and these findings suggest the need for additional investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…According to their study, they based the symptoms from the respiratory system on the responses from the questionnaire. The lack of validated diagnosis probably decreased the explained variability of FeNO; however, their study reflected the study performed in the epidemiological conditions [ 23 ]. In the study performed by Garcia-Marcos, it was revealed that approximately 27% of the variability in FeNO levels could be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the in the author's previous study, the conclusion considered FeNO measurement as not a good screening tool for pediatric asthma in a community setting [23]. However, the current results of this study show that children with asthma-like symptoms and elevated FeNO levels are at increased risk of asthma and need further investigation, such results have been presented in the cross-sectional screening study conducted by Prasad et.…”
Section: Discussionmentioning
confidence: 58%
“…[24]. According to their study, they based the symptoms from the respiratory system on the responses from the questionnaire The lack of validated diagnosis probably decreased the explained variability of FeNO, however, their study re ected the study performed in the epidemiological con-ditions [23]. In the study performed by Garcia-Marcos, the variability of FeNO was ex-plained in 27%.…”
Section: Discussionmentioning
confidence: 99%